Oil injection for cosmetic enhancement of the upper extremities: a case report and review of literature: Upper Extremity Injections for Cosmetic Enhancement - Sisti, Andrea; Huayllani, Maria T.; Restrepo, David J.; Boczar, Daniel; Manrique, Oscar J.; Broer, Peter N.; Shapiro, Shane A.; Forte, Antonio J. (Acta Biomedica Atenei Parmensis, 2020)
Here the authors report a case of complications occured after injection of a site enhancement oil in the upper extremity for cosmetic muscles’ volume enhancement and a literature review on the topic. The medical and sports communities should be aware of the secondary effects of site enhancement oils use, which could bring to severe complications.